2005
DOI: 10.1210/jc.2005-0437
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin Levels of Obese and Lean Children and Adolescents: Biochemical Analysis and Clinical Relevance

Abstract: Resistin appears to be not the main link between obesity and insulin resistance in children and adolescents but because of its association with Tanner stage, it may be related to the maturation of children during pubertal development. Additionally, we have demonstrated the presence of different molecular isoforms of resistin in human blood, and this may raise problems in comparing data from diverse assay systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
132
8
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 38 publications
(57 reference statements)
21
132
8
18
Order By: Relevance
“…Circulating resistin was reported to be elevated in human obesity in some, [3][4][5] but not in all studies. [6][7][8] Positive correlations of circulating resistin and insulin resistance 9,10 could not be confirmed in other studies. 7,11 These findings suggest that the role of resistin in the etiology of obesity and insulin resistance in humans -if there is any -is much more complex than in mice and other rodents.…”
Section: Introductionmentioning
confidence: 72%
“…Circulating resistin was reported to be elevated in human obesity in some, [3][4][5] but not in all studies. [6][7][8] Positive correlations of circulating resistin and insulin resistance 9,10 could not be confirmed in other studies. 7,11 These findings suggest that the role of resistin in the etiology of obesity and insulin resistance in humans -if there is any -is much more complex than in mice and other rodents.…”
Section: Introductionmentioning
confidence: 72%
“…2,3 The adipocyte-derived hormones resistin, adiponectin and leptin may play a role in the development of hypertension and/or insulin resistance. [4][5][6][7] Among children, inverse associations of adiponectin or resistin with body mass index (BMI) and insulin resistance have been reported, 8 but not all studies agree. 9 Studies on diet in childhood hypertension have mainly focused on sodium or calcium intake, rather than macronutrients.…”
Section: Hypertension Insulin Resistance Resistin and Adiponectinmentioning
confidence: 99%
“…4 Resistin promotes the release of endothelin-1, a potent vasoconstrictor, from endothelial cells, 20 although the resistin-like molecule-a has vasoconstrictive properties. 21 The relationship between resistin, adiponectin, adiposity and insulin resistance in humans is unclear; 22 several studies in adults have found resistin or adiponectin concentrations predict insulin resistance, 8,23 whereas others have not. 24 Several pediatric studies have not reported an association between resistin or adiponectin and weight status, leptin or insulin concentrations.…”
Section: Hypertension Insulin Resistance Resistin and Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Human resistin has a tendency to form oligomers that are, in contrast to mice, biologically 6 more active [15,16,17]. However, both the oligomeric and dimeric forms of resistin are able to activate tumor necrosis factor (TNF)-α and interleukin (IL)-12 in macrophages and monocytes [18].…”
mentioning
confidence: 99%